2014
DOI: 10.1557/jmr.2014.361
|View full text |Cite
|
Sign up to set email alerts
|

Highly piezoresistive compliant nanofibrous sensors for tactile and epidermal electronic applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Another modality for HR monitoring which is coming to focus in the recent years is the application of flexible strain or pressure sensors. Soltanian et al [ 13 ] reported a soft and conformable strain sensor made from a mesh of conductive nanofiber (NF) encapsulated in an elastomer ( Figure 4 a). Flexible piezoresistive sensors (FPS), which are manufactured using electrospinning—a versatile method for economic nanomaterial fabrication—demonstrates a fast, low-voltage, accurate, repeatable strain sensing behavior with a strain gauge factor as high as 60 ( Figure 4 b).…”
Section: Vital Sign Monitoringmentioning
confidence: 99%
See 4 more Smart Citations
“…Another modality for HR monitoring which is coming to focus in the recent years is the application of flexible strain or pressure sensors. Soltanian et al [ 13 ] reported a soft and conformable strain sensor made from a mesh of conductive nanofiber (NF) encapsulated in an elastomer ( Figure 4 a). Flexible piezoresistive sensors (FPS), which are manufactured using electrospinning—a versatile method for economic nanomaterial fabrication—demonstrates a fast, low-voltage, accurate, repeatable strain sensing behavior with a strain gauge factor as high as 60 ( Figure 4 b).…”
Section: Vital Sign Monitoringmentioning
confidence: 99%
“…Flexible piezoresistive sensors (FPS), which are manufactured using electrospinning—a versatile method for economic nanomaterial fabrication—demonstrates a fast, low-voltage, accurate, repeatable strain sensing behavior with a strain gauge factor as high as 60 ( Figure 4 b). Low power sensor operation down to μW will be feasible using this sensor [ 13 ]. The strain-sensitivity is attributed to the reversible disjointing/jointing of inter-NF junctions held together by a spring action of the encapsulating elastomer.…”
Section: Vital Sign Monitoringmentioning
confidence: 99%
See 3 more Smart Citations